Adapting an Interprofessional Training Model for Social Work Field Placements: An Answer for Better Mental Health Care Outreach for Older Adults in Primary Care. Issue 5 (20th October 2017) - Shah, Avani; Wharton, Tracy; Scogin, Forrest
ABSTRACT: Professional shortages of geriatrically trained social workers pose a barrier to mental health care for older adults. Integrating graduate social work interns into primary care settings may increase the availability of trained social workers. However, few studies provide guidance on how to develop an interprofessional healthcare placement focused on the needs of older adults. This article discusses a model training program created by a psychology department (with input from social work faculty) that can be adapted by schools of social work. Client outcomes ( n = 47) indicate significant improvement when using this model.